Parents' educational stress and its nomological network. - Duan, Jinyun; Liang, Fenghua; Wang, Xiaotian; Xu, Ran (British Journal of Psychology, 2025)
Although parents' educational stress has become a buzzing problem for Chinese parents and society in recent years, it is underresearched. To fill this gap, we first conceptualize the construct of parents' educational stress. Then, we use a multi‐study scale development process to develop and validate a two‐dimensional parents' educational stress scale. Moreover, drawing from social comparison theory, we explore this new construct's preliminary nomological network by examining its antecedents and consequences (controlling parenting and family‐to‐work conflict). Overall, our research suggests that the parents' educational stress scale is a reliable scale that can be used to assess this widespread phenomenon and that parents' educational stress has detrimental effects on parents' parenting style and work behaviour.